Bacteriobilia and fungibilia are associated with outcome in patients with endoscopic treatment of biliary complications after liver transplantation - Gotthardt, Daniel; Weiss, Karl Heinz; Rupp, Christian; Bode, Konrad A.; Eckerle, Isabella; Rudolph, Gerda; Bergemann, Janine; Klöters-Plachky, Petra; Chahoud, Fadi; Büchler, Markus W.; Schemmer, Peter; Stremmel, Wolfgang; et al. (Endoscopy, 2013)
Background and study aims: To determine the importance of bacteriobilia and fungibilia in patients with endoscopic treatment of biliary complications after orthotopic liver transplantation (OLT). Patients and methods: In a prospective study at a tertiary center, 213 patients underwent 857 endoscopic retrograde cholangiographies (ERCs) after OLT. Findings at first ERC were: anastomotic stricture in 24.4 %, nonanastomotic stricture in 18.3 %, leakage in 11.3 %, and gallstones in 4.7 %. Results: Bile samples from first ERC showed Gram-positive bacterial isolates in 102/180 (57 %) and Gram-negative in 44/180 (24 %). Main species were Enterococcus spp. (40 %; 72/180) and Escherichia coli (10 %; 18 /180). Enteric bacteria (present in 47 %) and Candida spp. (present in 18 %) were both associated with clinical signs of cholangitis, but not with laboratory signs of inflammation. Multiresistant strains (present in12 % of samples) showed no association with clinical or laboratory parameters. Detection of microbiological isolates was independent of endoscopic findings and treatment. In patients with successful endoscopic intervention, the actuarial survival free of retransplantation was significantly lower in those with detection of enteric bacteria, being 51.8 months (95 % confidence interval [CI] 42.9 - 60.6) vs. 62.9 months (95 %CI 59.1 - 66.7); P = 0.025). Fungibilia was associated with significantly lower actuarial retransplantation-free survival, independently of successful endoscopic treatment (mean 35.1 months [95 %CI 23.5 - 46.7] vs. 53.1 months [(95 %CI 48.0 - 58.2]; P = 0.019). Conclusions: Bacteriobilia and fungibilia can frequently be detected by routine microbiological sampling in patients after OLT. Regular bile sampling is recommended since the presence of difficult-to-treat multiresistant strains is unpredictable. Survival is affected by this altered biliary microbiological environment after OLT.